ENHANCING STUDENTS’ ESSAY WRITING SKILLS THROUGH THE IELTS TASK 2 MODEL ESSAY APPROACH - Agus Supriyadi; Indry Widyasti Anwar; Magvirah Octasary; Wang Xiaoqian; Eka Wahjuningsih (University of Kuningan, 2025)
This study investigates the effectiveness of using IELTS Writing Task 2 model essays as a pedagogical tool to enhance students' academic essay writing skills. Recognizing the challenges many learners face in organizing ideas, developing arguments, and using appropriate academic language langusge, this research explorer how exposure to high-quality model essays can improve students' writing performance. A classroom based intervention was conducted with undergraduate English language leaners, incoperating model essays analysis, guided practice, and peer feedback. Pre and post intervention writing assessment, along with student reflections, were used to evaluate the impact. The results of this study indicate that using IELTS Writing Task 2 as a model for essay instruction leads to a statistically and pedagogically significant improvement in students' writing abilities. The mean score for the pre-test was 3.95 (SD=0.78), and the post test mean rose to 4.70 (SD=0.67). The difference was statistically significant with p < 0.001. The finding indicate that students demonstrated notable improvements in coherence, cohesion, cocabulary usage, and task response. Moreover, students reported increased confidence and better understanding of essay structure and argumentation techniques. This study concludes that integrating IELTS Test 2 model essays into writing instruction is an effective strategy for developing students' academic writing competence.